2010
DOI: 10.4049/jimmunol.0901783
|View full text |Cite
|
Sign up to set email alerts
|

Context-Dependent Regulation of Hematopoietic Lineage Choice by HEBAlt

Abstract: Material

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 71 publications
1
14
0
Order By: Relevance
“…However, both isoforms contain DNA binding and dimerization domains, indicating separate functions of the isoforms, and not a simple dominant negative function of the short isoform. Indeed, both the long and short isoform of the TCF12 have previously been described as having distinct functions in thymocyte development [31,32]. Deregulation of Tcf12 has recently been causally implicated in CRC in a DNA transposon based forward genetic screen in a mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…However, both isoforms contain DNA binding and dimerization domains, indicating separate functions of the isoforms, and not a simple dominant negative function of the short isoform. Indeed, both the long and short isoform of the TCF12 have previously been described as having distinct functions in thymocyte development [31,32]. Deregulation of Tcf12 has recently been causally implicated in CRC in a DNA transposon based forward genetic screen in a mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…HEBAlt, a long form of the E protein HEB gene, is specifically expressed in lymphoid precursor cells [34]. In thymic precursors, HEBAlt collaborates with Notch signals to promote early T cell development by suppressing B cell or myeloid potential [35][36]. HEB −/− T cells possess compromised Notch1 function and lose T cell potential [37].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that HEBAlt-expressing fetal liver-derived LSK cells are inhibited from becoming B cells and myeloid cells in the presence of high levels of Dll1 (Wang et al, 2010). HEBAlt is upregulated by Notch signaling, suggesting that it could influence DC development.…”
Section: Hebalt Inhibits DC Developmentmentioning
confidence: 99%
“…E2-2 has been shown to play a role in splenic pDC development (Cisse et al, 2008), but the influences of the other E proteins on DC development are unknown. HEBAlt promotes T-cell development downstream of Dll-Notch signaling (Bain et al, 1997;Wang et al, 2010;Wang et al, 2006), and is thus a good candidate for influencing the T/DC fate choice towards the T-cell lineage. Conversely, the E protein antagonist Id2, which is thought to be induced by PU.1 (Anderson et al, 2002), promotes DC development (Hacker et al, 2003).…”
Section: Introductionmentioning
confidence: 99%